Penilaian Pelajar Terhadap Kompetensi Pemimpin Program Pendidikan Luar Di Institut Pendidikan Guru Malaysia - Amrin, Azita (2007)
Outdoor Education leaders should possess various competencies from the three main skills agreed by professionals and researchers in the field, namely; hard skills, soft skills and conceptual skills. This study aims to evaluate students' evaluation on the instructors' competencies in the teaching and learning process of the Outdoor Education Program at the Malaysian Teacher Education Institutes. Based on Miller’s study (2002), five competencies from the three main skills are being evaluated, that is; Leadership skills, Technical skills, Risk Management skills, First Aids and Emergency skills, and Environmental skills. The Importance–Performance Analysis (IPA) model of evaluation (Martilla & James, 1977), is adopted in this study. Based on this model, respondents are required to evaluate the level of importance of each attribute of the competencies and the performance of the instructors based on the same competencies. The IPA model is used to combine the mean score of importance and performance evaluation to determine the strengths and weaknesses of the instructors in the teaching and learning process. The population of this study consists of 364 trainees from eight Teacher Education Institutes all over Malaysia. The instrument, in the form of a questionnaire is adapted and developed by the researcher based on studies from Attarian (1995), Buell (1983), Miller (2002), and Priest and Gass (1997). The range of the Cronbach Alfa reliability index from all the 89 attributes of the five competencies are from 0.80 to 0.98. The data are analysed using the SPSS-Windows version 11.5. Descriptive statistics in the form of percentage, mean and standard deviation are used to answer research questions one to ten, and inferential statistics of MANCOVA is used to answer research questions 11 and 12. The findings show that 74 (84.1%) attributes of the Outdoor Education competencies are perceived by the respondents as strengths in the teaching and learning process. Only 15 (15.9%) out of 89 attributes are perceived by the respondents to be the weaknesses of the teaching and learning process of the Outdoor Education Program. The findings also reveal that respondents’ prior experiences and involvement in the Outdoor Education Program do have an influence on the evaluation of the instructors’ performance in the teaching and learning process. However, gender and educational background do not have any influence on the evaluation of the importance and performance of each attribute of the competencies. Thus, this study recommend that the Outdoor Education Program in Teacher Education Institutes should be continued because the strengths outweigh the weaknesses in the teaching and learning process. This study also suggests that the quality of the instructors and the levels of competencies can be improved through in-house training and professional development.